Penggunaan Metode Control to Free untuk Meningkatkan Kemampuan Menulis Teks Deskripsi bagi Siswa Kelas VII-C SMP Islam Khadijah Bagek Nyaka - Qomariah, Nurul (Lembaga Yasin AlSys, 2022)
This study was conducted based on the fact that writing is the most difficult skill for students to master. Students face difficulties in learning writing. They are not sure of how to compose a setence, arrange sentences into good paragraphs, how to develope their ideas, they have lack of vocabulary and tend to use only certain words they have known in writing. They also apply incorrect grammar in their writing. Teacher considers that teaching writing is a difficult task. This action research is about teaching writing descriptive text by using control to free method to the seven graders students of SMP Islam Khadijah Bagek Nyaka in the academic year of 2022-2023. The aim of this study is to find out how control to free method can be implemented to improve students‟ skill in writing descriptive text. In order to achieve the objectives, an action research was designed and carried out in this study. The participants of this study were 28 students of class VII C of SMP Islam Khadijah Bagek Nyaka in the academic year of 2022-2023. Questionnaire, observation sheet, and writing tests were used as the instruments for collecting data. The results of the study showed significant improvement of the students’ achievement in writing descriptive text. It is proven by the average results in every test; pre test (47,89), the first cycle test (58,92), and post test (71.30). The students’ writing skill (organization, content, grammar, punctuation, and style and quality of expression) in each test increased, too. Moreover, the result of the observation sheet showed that control to free method changed the students’ learning behavior being better than before. Their enthusiasm during the learning process increased in each cycle. The analysis result of questionnaire showed that control to free technique was useful to most of students to improve their learning interest in writing descriptive text. Their perception changed positively after having the treatment. It meant that the use of control to free technique could ease their problem in writing English especially descriptive text. Based on the results of those research instruments, it can be concluded that using control to free method as a learning method gives significant improvement to students’ skill in writing descriptive text.